Monitoring system based on IEC standards for irradiance and module temperature measurements in photovoltaic systems - Carhuavilca, A.M.; Conde, L.A.; Berastain, A.E.; Montes-Romero, J.; Gosgot Angeles, W.; de la Casa, J.; Töfflinger, J.A.; Catano Sanchez, M.C. (IOP Publishing, 2021)
Monitoring photovoltaic (PV) systems is necessary to assure their proper functioning. Mostly automated data acquisition systems (DAQ) are used for this purpose. Obtained data from DAQ are important for analysing the energy behavior of PV systems with any anomalies that may appear. It helps investors to realize economic calculations which use to estimate the return on investment. The article aims to present an open-source system that allows the acquisition and reliable recording of meteorological parameters that influence in the energy production of PV installations. The measurement processes were tested by different methods in order to comply with the standards of the International Electrotechnical Commission (IEC).
Keywords: Photovoltaic system; Data acquisition; Systems engineering; Reliability engineering; Computer science; Irradiance; Energy (signal processing); Engineering; Electrical engineering; Operating system; https://purl.org/pe-repo/ocde/ford#2.02.00